On-Surface Synthesis II Proceedings of the International Workshop On-Surface Synthesis, San Sebastián, 27-30 June 2016 (Advances in Atom and Single Molecule Machines,, 2018)
On-surface synthesis is appearing as an extremely promising strategy to create organic nanoarchitectures with atomic precision. Molecular building blocks holding adequate functional groups are dosed onto surfaces that support or even drive their covalent linkage. The surface confinement and the frequent lack of solvents (most commonly being performed under vacuum conditions) create a completely new scenario fully complementary to conventional chemistry. In a pedagogical way and based on the most recent developments, this volume presents our current understanding in the field, addressing fundamental reaction mechanisms, synthetic strategies to influence the reactions according to our needs, as well as the ultimate growth and characterization of functional materials. Verging on chemistry, physics and materials science, the book is aimed at students and researchers interested in nanochemistry, surface science, supramolecular materials and molecular devices. Chapters "Mechanistic insights into surface-supported chemical reactions", "Reactivity on and of Graphene Layers: Scanning Probe Microscopy Reviels" and "Bottom-up fabrication of atomically precise graphene nanoribbons" of this book are available open access under a CC BY 4.0 license at link.springer.com.